2020
DOI: 10.1186/s12862-020-01692-7
|View full text |Cite
|
Sign up to set email alerts
|

Floral signals evolve in a predictable way under artificial and pollinator selection in Brassica rapa

Abstract: Background Angiosperms employ an astonishing variety of visual and olfactory floral signals that are generally thought to evolve under natural selection. Those morphological and chemical traits can form highly correlated sets of traits. It is not always clear which of these are used by pollinators as primary targets of selection and which would be indirectly selected by being linked to those primary targets. Quantitative genetics tools for predicting multiple traits response to selection have been developed si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…Yet all three species produce little to no floral scent, suggesting there can be quick breakdown of floral scent production following pollinator transitions. This observation is consistent with previous studies that have shown that floral scent often evolves rapidly in response to selection (Ramos and Schiestl 2019;Zu et al 2020;Liu et al 2024).…”
Section: Floral Scent Loss Is Not Driven By Gene Loss In Costussupporting
confidence: 93%
“…Yet all three species produce little to no floral scent, suggesting there can be quick breakdown of floral scent production following pollinator transitions. This observation is consistent with previous studies that have shown that floral scent often evolves rapidly in response to selection (Ramos and Schiestl 2019;Zu et al 2020;Liu et al 2024).…”
Section: Floral Scent Loss Is Not Driven By Gene Loss In Costussupporting
confidence: 93%
“…When genetic correlations oppose the direction of selection, evolutionary responses can be constrained (Conner, 2012;Etterson & Shaw, 2001;Lande & Arnold, 1983). Such constraints can be investigated through quantitative genetics using the G-matrix of additive genetic variances and covariances and the selection gradients, as has been done in a number of prior studies (Colautti & Barrett, 2011;Conner & Agrawal, 2005;Franks et al, 2012;Johnson et al, 2009;Smith & Rausher, 2008;Zu et al, 2020). Several different approaches have been used to quantify how much of a constraint would occur due to genetic correlations (Calsbeek & Goodnight, 2009), but a simple first approach is to compare direct and indirect selection, given that direct selection accounts for selection directly acting on a trait without accounting for correlations, while indirect selection includes selection driven by selection acting on other correlated traits (Conner & Hartl, 2004).…”
Section: Response To Selection Was Generally Not Constrained By Genet...mentioning
confidence: 99%
“…These are often found by decomposing G into independent axes, akin to principal components, representing directions in which phenotypes vary genetically ( Lande, 1979 ; Walsh & Blows, 2009 ). The primary axis of G , known as g max , is the direction of the phenotype in which genetic variation is most abundant and the direction in which phenotypic evolution is expected to occur ( Costa e Silva et al, 2020 ; McGlothlin et al, 2018 ; Schluter, 1996 ; Walter, 2023 ; Zu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%